Expanding the use and impact of the CLEANED tool for assessing environmental impact assessments of livestock enterprises - Notenbaert, An Maria Omer; van der Hoek, Rein; Mwema, Emmanuel; González, Ricardo; Cardoso, Juan Andrés (CGIAR System Organization, 2024)
CLEANED, an acronym for Comprehensive Livestock Environmental Assessment for improved Nutrition, a secured Environment and sustainable Development along livestock value chains, is a multi-dimensional modelling tool designed to produce rapid environmental impact assessments in mixed crop-livestock farming systems in developing countries. The use of CLEANED has been expanded and further developed under the Initiative on Livestock and Climate through three pathways. In Pathway 1, training events and workshops were conducted to teach new users how to use it effectively. In Pathway 2, more assessments were conducted using the tool to promote wider uptake in specific countries. In Pathway 3, the tool has been updated and improved.